Decolonising Management. Reflections of a Human Resource Practitioner from the Global South - Goh, Patrick (Murmurations: Journal of Transformative Systemic Practice, 2023)
This article takes a slight detour from this edition's theme – decolonising systemic practice – by suggesting that systemic practices can be used to decolonise dominant discourses, such as Western-centric management and its associated form of knowledge production. My views are voiced from an insider–outsider, intersectional positionality – a person from the Global South now working as a Human Resource Practitioner in the United Kingdom. The article posits management and human resource management as Western in their cultural roots and neoliberal in their economic worldview and proposes that underlying assumptions embedded in these discourses have resulted in epistemic othering and subjugation on an international scale. It suggests that decolonising management could begin with making the paradigm shift from a diagnostic to a dialogical understanding of organising human systems. It holds up this epiphany as an example of embracing indigenous knowledge and practices. The article also suggests, through a case story, the use of a systemic practice known as Social GRACEs (Burnham, 1992), that systemic reflexivity and the re-constitution of language games are paramount for making such a paradigmatic shift to decolonised practice.